10.8k views
3 votes
Let m = 6x + 5.

Which equation is equivalent to (6x + 5)2 - 10 = -182 – 15 in terms of m?

Choose 1 answer:

(A) m² – 3m + 5 = 0

m2 - 3m + 5 = 0

©

mº – 3m – 10 = 0

©

m

+3m - 10 = 0

User Atwellpub
by
6.1k points

1 Answer

4 votes

We have been given that
m=6x+5. We are asked to write
(6x + 5)^2-10 =-18x-15 in terms of m.

First of all, we will factor
-3 from right side of equation as:


(6x + 5)^2-10 =-3\cdot 6x-3\cdot 5


(6x + 5)^2-10 =-3( 6x+5)

Now we will substitute
m=6x+5 in our equation as:


(m)^2-10 =-3(m)


m^2-10 =-3m

Upon adding
3m on both sides, we will get:


m^2+3m-10 =-3m+3m


m^2+3m-10 =0

Therefore, the equation
m^2+3m-10 =0 is equivalent to
(6x + 5)^2-10 =-18x-15 in terms of m.

User Ironkeith
by
4.9k points